(untitled) (Global Journal of Human-Social Science, 2025)
This article presents a critical reflection on the evolving role of the Brazilian Sign Language Translator and Interpreter TIL within the national education system Adopting a historical lens it traces the trajectory from the early days of predominantly voluntary and community-based interpreting particularly in religious contexts to the current phase marked by professionalization through academic training and legal recognition The discussion explores the implications of this transition for the interpreter s relationship with the Deaf community the quality of linguistic mediation and the multifaceted demands of both technical and emotional preparedness in educational settings The article contends that the interpreter s role must transcend mere technical neutrality assuming an ethical cultural and transformative stance in promoting linguistic accessibility and inclusive education for Deaf students